Managing Facility Risk: External Threats and Health Care Organizations. (14th April 2014) - Reid, Daniel J.; Reid, William H.; Busch, Kenneth G.; Schouten, Ronald; Weissman, Sidney H.; Felthous, Alan R.
<x xml:space="preserve">Abstract</x> Clinicians and clinical administrators should have a basic understanding of physical and financial risk to mental health facilities related to external physical threat, including actions usually viewed as "terrorism" and much more common sources of violence. This article refers to threats from mentally ill persons and those acting out of bizarre or misguided "revenge, " extortionists and other outright criminals, and perpetrators usually identified as domestic or international terrorists. The principles apply both to relatively small and contained acts (such as a patient or ex‐patient attacking a staff member) and to much larger events (such as bombings and armed attack), and are relevant to facilities both within and outside the U.S. Patient care and accessibility to mental health services rest not only on clinical skills, but also on a place to practice them and an organized system supported by staff, physical facilities, and funding. Clinicians who have some familiarity with the non‐clinical requirements for care are in a position to support non‐clinical staff in preventing care from being interrupted by external threats or events such as terrorist activity, and/or to serve at the interface of facility operations and direct clinical care. Readers should note that this article is an introduction to the topic and cannot address all local, state and national standards for hospital safety, or insurance providers' individual facility requirements. Copyright © 2014 John Wiley & Sons, Ltd.